Effects of Psychotropic Agents on Extinction of Lever-Press Avoidance in a Rat Model of Anxiety Vulnerability - Jiao, Xilu; Beck, Kevin D.; Stewart, Amanda L.; Smith, Ian M.; Myers, Catherine E.; Servatius, Richard J.; Pang, Kevin C. H. (Frontiers in Behavioral Neuroscience, 2014)
Avoidance and its perseveration represent key features of anxiety disorders. Both pharmacological and behavioral approaches (i.e. anxiolytics and extinction therapy) have been utilized to modulate avoidance behavior in patients. However, the outcome has not always been desirable. Part of the reason is attributed to the diverse neuropathology of anxiety disorders. Here, we investigated the effect of psychotropic drugs that target various monoamine systems on extinction of avoidance behavior using lever-press avoidance task. Here we used the Wistar-Kyoto (WKY) rat, a unique rat model that exhibits facilitated avoidance and extinction resistance along with malfunction of the dopamine (DA) system. Sprague Dawley (SD) and WKY rats were trained to acquire lever-press avoidance. WKY rats acquired avoidance faster and to a higher level compared to SD rats. During pharmacological treatment, bupropion, and desipramine significantly reduced avoidance response selectively in WKY rats. However, after the discontinuation of drug treatment, only those WKY rats that were previously treated with desipramine exhibited lower avoidance response compared to the control group. In contrast, none of the psychotropic drugs facilitated avoidance extinction in SD rats. Instead, desipramine impaired avoidance extinction and increased non-reinforced response in SD rats. Interestingly, paroxetine, a widely used antidepressant and anxiolytic, exhibited the weakest effect in WKY rats and no effects at all in SD rats. Thus, our data suggest that malfunctions in brain catecholamine system could be one of the underlying etiologies of anxiety-like behavior, particularly avoidance perseveration. Pharmacological manipulation targeting DA and norepinephrine is more effective to facilitate extinction learning in this strain. The data from the present study may shed light on new pharmacological approaches to treat patients with anxiety disorders who are not responding to serotonin re-uptake inhibitors.